Determinants of Investment Decisions Among Generation Z: The Role of Financial Literacy, Financial Inclusion and Fintech - Rachmi Meutia; Ahmad Rochied; Uliya Azra (Jurnal Manajemen dan Profesional, 2026)
The dynamics of financial decision-making among Generation Z have emerged as a primary focus, driven by their surging demographic proportion within the working-age population and the rapid digital transformation in the financial sector. This study was conducted to evaluate the impact of financial literacy, financial inclusion, and the adoption of financial technology on the investment decisions of Generation Z in Banda Aceh City. Using a quantitative design and purposive sampling, data was collected from 100 Generation Z capital market investors. Statistical analyses demonstrated that financial literacy, financial inclusion, and financial technology exert a positive and significant influence on investment decisions, both partially and simultaneously. Ultimately, these findings highlight the necessity of enhancing financial education, expanding facility access, and leveraging digital platforms to optimize financial decision-making among the younger generation.